Asclepias tuberosa Butterfly Weed, Indian Paintbrush: FPS050/FP050, 8/2018 - Gilman, Edward; Klein, Ryan W.; Hansen, Gail (EDIS, 2018)
This document provides a comprehensive overview of the butterfly weed (Asclepias tuberosa), a member of the milkweed family. It details the plant’s characteristics, including its growth habits, flowering period, and preferred growing conditions. The butterfly weed is noted for its vibrant orange, red, and yellow flowers, which attract butterflies and hummingbirds. The document also covers the plant’s uses, propagation methods, and potential pest issues. Additionally, it highlights the plant’s medicinal uses and its tendency to self-seed and escape cultivation. Original publication date October 1999.